Copolyester masterbatch for general pet transparent toughening modification and its preparation method
Patent Information
- Application Number
- CN202611344158.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-16
AI Technical Summary
[0008]本发明涉及用于通用PET透明增韧改性的共聚酯母粒及其制备方法,解决了现有PET共聚、物理共混两大主流改性技术,分别存在耐热与韧性相互制衡、透明性损耗大或增韧效率低的问题,无法同步实现材料高透明、高韧性、高耐热的协同性能提升,制约了改性PET在高端领域应用的问题
[0027] This invention achieves a synergistic balance between heat resistance and toughness, solves the inherent defects of single components, and offsets the Tg decrease caused by BEPD through the rigid helical structure of SPG. The flexible branched chain of BEPD improves the brittleness of the SPG system, and the modified PET can stably maintain Tg≥70℃ and elongation at break of over 280%, thus solving the bottleneck in the industry where heat resistance and toughness cannot be balanced.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyester modified polymer materials technology, and in particular to copolyester masterbatch for general-purpose transparent toughening modification of PET and its preparation method. Background Technology
[0002] Polyethylene terephthalate (PET), as the most produced saturated thermoplastic polyester material, has excellent chemical corrosion resistance, mechanical strength, thermal stability and electrical insulation properties. With its comprehensive performance advantages, it has been widely used in many industrial and consumer fields such as chemical fiber textiles, food packaging, optical films, electronic devices, and automotive parts. It is one of the most widely used categories of polymer materials.
[0003] However, due to its inherent molecular structure, pure PET materials have significant performance limitations, hindering their large-scale application in high-end fields. The high proportion of rigid benzene rings in the PET molecular chain, along with its high molecular chain regularity and lack of branching, results in significant brittleness, with an elongation at break of only 50%–150%, low notched impact strength, and insufficient impact and flexural toughness. Furthermore, PET's rapid crystallization rate and high crystallinity make it highly susceptible to defects such as crystal points and whitening during melt processing, making it unable to simultaneously meet the composite performance requirements of high transparency, high toughness, and high heat resistance in high-end optics, high-end food packaging, and precision electronics.
[0004] Currently, the industry's modification technologies for PET performance defects are mainly divided into two major routes: copolymer modification and physical blending toughening masterbatch modification. However, both existing technologies have inherent technical defects and cannot achieve synergistic optimization of PET's overall performance. The specific defects are as follows:
[0005] Firstly, the copolymerization modification route presents a performance trade-off, making it difficult to balance heat resistance and toughness. Existing diol copolymerization monomers each have performance shortcomings, failing to achieve synergistic performance improvements: 1) Copolymerization modification with the rigid monomer spirocyclic diol (SPG) can significantly increase the glass transition temperature of the polyester matrix using its unique spirocyclic rigid structure, achieving a Tg ≥ 90℃ and effectively preserving and improving the material's heat resistance. However, the modified material becomes excessively rigid, further exacerbating brittleness, with an elongation at break below 100%, making it completely unsuitable for high-toughness applications; 2) Copolymerization modification with the flexible monomer 2-butyl-2-ethyl-1,3-propanediol (BEPD) can effectively improve performance by introducing asymmetric alkyl branches. Regarding material toughness, when the BEPD doping amount is 10 mol%, the elongation at break of modified PET can reach 499%. However, this modification method will significantly destroy the regularity of PET molecular chains, causing the glass transition temperature of the material to drop sharply to 60-65℃, and the heat resistance performance will be greatly reduced, which cannot meet the requirements of heat resistance conditions. 3) Using conventional diol copolymerization modification such as 1,4-cyclohexanediol (CHDM), 2-methyl-1,3-propanediol (MPD), and neopentyl glycol (NPG) generally presents a core contradiction between toughening modification and heat resistance modification, and it has always been impossible to break through the performance balance bottleneck.
[0006] Secondly, the physical blending toughening masterbatch modification route suffers from severe transparency loss and low toughening efficiency. Currently, commercially available PET toughening masterbatches mainly use thermoplastic polyester elastomer (TPEE), methyl methacrylate-butadiene-styrene copolymer (MBS), and acrylate elastomers as core toughening components. These elastomer components have significant refractive index differences from the PET matrix, resulting in dispersed phase sizes larger than 200 nm after blending. This leads to severe light scattering, ultimately causing the blended material's haze to exceed 20%, significantly reducing its transparency and making it unsuitable for high-end transparent applications. Furthermore, while existing PCTG-PET blends can largely retain the material's light transmittance, their toughening efficiency is extremely low, offering very limited improvement in PET material toughness and failing to address the core issue of insufficient toughness in the PET matrix itself.
[0007] In summary, existing PET modification technologies generally suffer from technical barriers due to the optimization of a single performance and the mutual sacrifice of core properties: rigid copolymer modification sacrifices material toughness, flexible copolymer modification sacrifices material heat resistance, and elastomer blend modification sacrifices material transparency. Relying on existing single-monomer modification or masterbatch modification technologies, it is impossible to simultaneously achieve a composite performance improvement of high transparency, high toughness, and high heat resistance retention in PET materials. This greatly limits the widespread application of modified PET materials in high-precision manufacturing, high-end optics, high-end food packaging, and other fields with high precision and high performance requirements. Therefore, there is an urgent need to develop a PET modification technology that can synergistically balance transparency, toughness, and heat resistance. Summary of the Invention
[0008] This invention relates to copolyester masterbatch for transparent toughening modification of general-purpose PET and its preparation method. It solves the problems of existing PET copolymerization and physical blending modification technologies, which have the problems of mutual balancing of heat resistance and toughness, large loss of transparency or low toughening efficiency. They cannot simultaneously achieve the synergistic improvement of high transparency, high toughness and high heat resistance of materials, thus restricting the application of modified PET in high-end fields.
[0009] This invention provides a copolyester masterbatch for general-purpose transparent toughening modification of PET, which is obtained by melt polycondensation of a dicarboxylic acid component and a diol component;
[0010] Based on 100% of the total molar amount of the dicarboxylic acid component, it contains: 80-100 mol% terephthalic acid residues, and optionally 0-20 mol% modified aromatic dicarboxylic acid residues;
[0011] Based on 100% of the total molar amount of the diol component, it is composed of the following residues: 5-40 mol% SPG residues, 5-40 mol% BEPD residues, and 20-90 mol% EG residues.
[0012] Furthermore, in the diol component, the molar ratio of SPG to BEPD is 1:0.5 to 2.
[0013] Furthermore, catalysts and heat stabilizers are added during the melt polycondensation process.
[0014] Furthermore, the catalyst is selected from at least one of tetrabutyl titanate, antimony trioxide, and antimony glycolate, and the amount added is 0.01 to 0.08% of the mass of terephthalic acid.
[0015] Furthermore, the heat stabilizer is selected from at least one of trimethyl phosphate and triphenyl phosphate, and the amount added is 0.01 to 0.05% of the mass of terephthalic acid.
[0016] A method for preparing copolyester masterbatch for general-purpose transparent toughening modification of PET includes the following steps:
[0017] Step 1, esterification reaction:
[0018] Terephthalic acid and EG were added to a polymerization reactor at a molar ratio of 1:1.2-1.5 and esterified at 240-250℃ and 0.2-0.3MPa. The fraction was collected until the esterification rate was ≥95% to obtain the esterified product.
[0019] Step 2, SPG prepolymerization:
[0020] Add all SPG to the esterification product, along with a catalyst and a heat stabilizer; heat to 260–270°C and apply a gradient vacuum; first, maintain the temperature at 1000 Pa for 10–15 min to remove low-boiling substances, then reduce the pressure to <100 Pa and prepolymerize for 0.5–1.5 h to obtain the prepolymer.
[0021] Step 3: BEPD final condensation polymerization:
[0022] All BEPD is added to the prepolymer under normal or slightly positive pressure, the temperature is raised to 270-280℃, and polycondensation is carried out under vacuum <50Pa for 3-5 hours until the intrinsic viscosity of the product is 0.65-0.85dL / g; the product is discharged under nitrogen to break the vacuum, granulated by water cooling, and dried at 60-80℃ to obtain copolyester masterbatch.
[0023] Furthermore, BEPD incorporates prepolymers under normal or slightly positive pressure to prevent loss during high-vacuum extraction.
[0024] A transparent toughened modified PET composition is prepared by melt blending general-purpose PET chips with copolyester masterbatch; the amount of copolyester masterbatch added is 5-40 wt% based on the total mass of the composition.
[0025] Furthermore, an ester exchange catalyst is added during the melt blending process; the ester exchange catalyst is selected from at least one of tetrabutyl titanate, zinc acetate, and manganese acetate, and the amount added is 0.05 to 0.2 wt% of the total mass of PET and copolyester masterbatch.
[0026] This invention provides a copolyester masterbatch for general-purpose transparent toughening modification of PET and its preparation method, which has the following beneficial effects:
[0027] This invention achieves a synergistic balance between heat resistance and toughness, solves the inherent defects of single components, and offsets the Tg decrease caused by BEPD through the rigid helical structure of SPG. The flexible branched chain of BEPD improves the brittleness of the SPG system, and the modified PET can stably maintain Tg≥70℃ and elongation at break of over 280%, thus solving the bottleneck in the industry where heat resistance and toughness cannot be balanced.
[0028] This invention achieves both high transparency and low haze, outperforming traditional elastomer toughening systems. The copolyester masterbatch and PET are homologous polyesters with excellent compatibility. After blending, the dispersed phase size is controlled below the visible light wavelength, resulting in a modified material with a light transmittance of ≥83% and a maximum haze of only 17%. Compared to elastomer masterbatches, this represents a more than 10% increase in light transmittance and a 50% reduction in haze.
[0029] This invention first introduces SPG to construct rigid segments, and then adds BEPD at atmospheric pressure to introduce flexible branches, precisely controlling the molecular sequence distribution. Compared with one-time feeding polymerization, the modified material has a 27% increase in elongation at break and a 3 percentage point increase in light transmittance. The product batch stability is also higher. Furthermore, a small amount of transesterification catalyst is added during melt blending to promote appropriate transesterification between the two phases, refine the dispersed phase structure, and simultaneously improve impact and tensile toughness, further reducing haze. Ordinary blending or reactive blending processes can be flexibly selected according to product requirements.
[0030] This invention utilizes the combination of SPG and BEPD, which has a unique synergistic effect. Compared with diol combinations such as SPG+MPD and CHDM+BEPD, the material exhibits a greater increase in elongation at break and notched impact strength at the same addition ratio. Other diol compound systems cannot achieve the same modification effect. Detailed Implementation
[0031] This invention proposes a copolyester masterbatch for general-purpose transparent toughening modification of PET, prepared by melt stepwise polycondensation of dicarboxylic acid component and diol component:
[0032] Step 1, Dicarboxylic acid component (total molar 100%): 80-100 mol% terephthalic acid residues, with optional aromatic modified dicarboxylic acid residues of 0-20 mol%
[0033] Step 2: The diol component (total molar 100%) consists of three types of monomer residues:
[0034] Spirocyclic diol (SPG) residues: 5–40 mol%, preferably 15–30 mol%, providing a rigid structure to increase Tg and inhibit crystallization;
[0035] BEPD residues: 5–40 mol%, preferably 10–25 mol%, asymmetric branches enhance molecular chain flexibility and elongation at break;
[0036] Ethylene glycol (EG) residues: 20–90 mol%, preferably 45–75 mol%, to maintain the polyester main chain structure and processing fluidity;
[0037] Step 3, Key Ratio: SPG to BEPD molar ratio 1:0.5~2;
[0038] A stepwise melt polycondensation method for preparing copolyester masterbatch:
[0039] The process involves three steps: esterification, SPG prepolymerization, and BEPD final polymerization.
[0040] Step 1, Esterification reaction: Terephthalic acid and ethylene glycol are added to the polymerization reactor at a molar ratio of 1:1.2-1.5, and esterification is carried out at 240-250℃ and 0.2-0.3MPa. The fraction is collected until the esterification rate is ≥95% to obtain the esterified product.
[0041] Step 2, SPG prepolymerization: Add all SPG to the esterification product, along with polyester catalyst and heat stabilizer; raise the temperature to 260-270℃ and apply a vacuum gradient, first hold at 1000Pa for 10-15 minutes to remove low-boiling substances, then reduce the pressure to <100Pa for 0.5-1.5 hours of prepolymerization to obtain rigid segment prepolymer.
[0042] The catalyst is selected from tetrabutyl titanate, antimony trioxide, and antimony glycolate, and the addition amount is 0.01-0.08% of the mass of terephthalic acid; the heat stabilizer is trimethyl phosphate and triphenyl phosphate, and the addition amount is 0.01-0.05%.
[0043] Step 3, final polycondensation of BEPD: Add all BEPD under normal / slight positive pressure, heat to 270-280℃, polycondense under vacuum <50Pa for 3-5 hours, and monitor the stirring power until the intrinsic viscosity of the product is 0.65-0.85dL / g; break the vacuum with nitrogen, granulate with water cooling, and dry at low temperature of 60-80℃ to obtain masterbatch.
[0044] A transparent toughened modified PET composition:
[0045] The above copolyester masterbatch is melt-blended with general-purpose PET chips to obtain modified PET material. The masterbatch addition amount is 5-40 wt%, preferably 15-30 wt%.
[0046] Preparation method of transparent toughened PET composition:
[0047] Step 1: Drying pretreatment: Dry the copolymer masterbatch at 60-80℃, and dry the general PET chips at 120℃ to remove water.
[0048] Step 2, Material Mixing: The masterbatch is uniformly mixed with PET at a ratio of 5-40 wt%.
[0049] Step 3: Twin-screw melt blending: processing temperature 260-280℃, screw speed 300-600rpm, material residence time 2-5min; extrusion, water cooling, pelletizing and drying;
[0050] Step 4: Optimize the reactive blending process: Add an ester exchange catalyst (one or more of tetrabutyl titanate, zinc acetate, and manganese acetate) to the system. The amount added is 0.05-0.2 wt% of the total mass of the materials to promote the ester exchange between the two phases, refine the dispersed phase, and improve the interfacial bonding force.
[0051] The aforementioned copolyester masterbatch is used for transparent toughening modification of general-purpose PET to prepare highly transparent and tough food packaging, optical films, electronic device housings, and thin-walled injection molded products.
[0052] Test standards and conditions:
[0053]
[0054] Example of copolyester masterbatch preparation:
[0055] Example 1: Preparation of copolymer masterbatch (SPG 20 mol%, BEPD 15 mol%, EG 65 mol%)
[0056] Step 1, Esterification: PTA and EG are esterified at a molar ratio of 1:1.3 at 245℃ and 0.25MPa until the esterification rate reaches 96%;
[0057] Step 2, Pre-polymerization: Add all SPG, 0.04% tetrabutyl titanate, and 0.03% triphenyl phosphate; perform gradient vacuum pre-polymerization at 265℃ for 1 hour;
[0058] Step 3, final polycondensation: BEPD is added under normal pressure, and polycondensation is carried out at 275℃ and 40Pa for 4 hours, with a viscosity of 0.76 dL / g; the masterbatch is obtained by drying at 70℃.
[0059] The performance indicators of the masterbatch are as follows:
[0060]
[0061] Example 2: High SPG content masterbatch (SPG 32mol%, BEPD 12mol%, EG 56mol%)
[0062] Using the same stepwise polymerization process as in Example 1, the masterbatch performance indicators are as follows:
[0063]
[0064] Example 3: High BEPD content masterbatch (SPG 8mol%, BEPD 25mol%, EG 67mol%)
[0065] Using the same stepwise polymerization process as in Example 1, the masterbatch performance indicators are as follows:
[0066]
[0067] Examples of transparent toughened modified PET compositions:
[0068] Example 4: Modified PET (masterbatch addition 20wt%, masterbatch is from Example 1, ordinary physical blend without transesterification catalyst), performance indicators are as follows:
[0069]
[0070] Example 5: Modified PET (masterbatch addition 30wt%, masterbatch is from Example 1, ordinary physical blending), performance indicators are as follows:
[0071]
[0072] Example 6: Reactive blend modified PET (reactive blend, with the addition of 0.1 wt% zinc acetate transesterification catalyst and 20 wt% Example 1 masterbatch), performance indicators are as follows:
[0073]
[0074] Comparative Example (Existing Technical Solution)
[0075] Comparative Example 1: Pure General Purpose PET
[0076] Elongation at break: 125%; Notched impact strength: 3.8 kJ / m 2 Light transmittance 89.2%, haze 8.5%, Tg 76.2℃.
[0077] Comparative Example 2: Elastomer Masterbatch E-MA-GMA Modified PET (20wt% Added):
[0078] Elongation at break: 268%; Notched impact strength: 7.2 kJ / m 2 The light transmittance is 76.5%, the haze is 23.6%, and the Tg is about 76℃ (the Tg of the PET phase does not change, but an elastomer transformation occurs at low temperature).
[0079] Comparative Example 3: BEPD copolyester masterbatch (without SPG) modified PET (20wt% added)
[0080] BEPD masterbatch diol composition: BEPD 15 mol%, EG 85 mol% (synthesized according to Xue et al. method, BEPD copolyester Tg measured at approximately 63℃):
[0081]
[0082] Tg correction notes: When 20wt% of BEPD masterbatch (Tg≈63℃) is blended with PET (Tg76.2℃), the Tg of a single component in the compatible system is estimated to be approximately 73-74℃ according to the Fox equation, and the actual measured Tg is approximately 73℃.
[0083] Comparative Example 4: SPG copolyester masterbatch (without BEPD) modified PET (20wt% added)
[0084] SPG masterbatch diol composition: SPG 20 mol%, EG 80 mol% (SPG copolyester Tg measured at approximately 85℃):
[0085]
[0086] Comparative Example 5: Physical blending modification of PCTG and PET (20wt% addition):
[0087]
[0088] Comparative Example 6: SPG+BEPD one-time feeding copolyester masterbatch (no step-by-step process)
[0089] SPG 20mol%, BEPD 15mol%, EG 65mol% and terephthalic acid were added in a single batch using a conventional polymerization process. Blend (20wt% added):
[0090]
[0091] Comparative Example 7: SPG+MPD copolyester masterbatch modified PET (20wt% addition)
[0092] SPG 20mol%, MPD 15mol%, EG 65mol% copolyester masterbatch:
[0093]
[0094] Comparative Example 8: CHDM+BEPD copolyester masterbatch modified PET (20wt% addition)
[0095] CHDM 20mol%, BEPD 15mol%, EG 65mol% copolyester masterbatch:
[0096]
[0097] Summary table of performance comparisons for all samples:
[0098]
[0099]
[0100] Tg Unified Explanation: The blends of this invention are compatible and transparent systems (TEM observed dispersed phase size of 30-80nm, but DSC showed a single Tg). The Tg of the blends are all between that of pure PET (76.2℃) and masterbatch (81℃), which is in line with the prediction range of the Fox equation, and there are no outliers below 76.2℃.
[0101] Key comparative conclusions:
[0102] 1. Compared with elastomer masterbatch (Comparative Example 2): the transmittance of the present invention is increased by about 11 percentage points, the haze is reduced by about 52%, and the Tg of the PET phase is maintained well;
[0103] 2. Compared with BEPD masterbatch (Comparative Example 3): The Tg of this invention is increased by about 4°C, the heat resistance is significantly improved, and the elongation at break is maintained at over 300%;
[0104] 3. Compared with SPG masterbatch (Comparative Example 4): the elongation at break of the present invention is increased by about 120%, and the toughness is significantly enhanced;
[0105] 4. Compared with PCTG masterbatch (Comparative Example 5): the elongation at break of the present invention is increased by approximately 69%, and the impact strength is increased by approximately 65%;
[0106] 5. Compared with one-time feeding (Comparative Example 6): the elongation at break of the present invention is increased by about 27% and the light transmittance is increased by about 3 percentage points, proving the key role of the step-by-step feeding process;
[0107] 6. Compared with other monomer combinations (Comparative Examples 7 and 8): the elongation at break of the SPG+BEPD combination is about 58% higher than that of SPG+MPD, and the impact strength is about 32% higher than that of CHDM+BEPD, proving that the specific combination of SPG and BEPD has an irreplaceable synergistic effect.
Claims
1. A copolyester masterbatch for general-purpose transparent toughening modification of PET, characterized in that, It is prepared by melt polycondensation of a dicarboxylic acid component and a diol component; Based on 100% of the total molar amount of the dicarboxylic acid component, it contains: 80-100 mol% terephthalic acid residues, and optionally 0-20 mol% modified aromatic dicarboxylic acid residues; Based on 100% of the total molar amount of the diol component, it is composed of the following residues: 5-40 mol% SPG residues, 5-40 mol% BEPD residues, and 20-90 mol% EG residues.
2. The copolyester masterbatch for general-purpose transparent toughening modification of PET according to claim 1, characterized in that, In the diol component, the molar ratio of SPG to BEPD is 1:0.5 to 2.
3. The copolyester masterbatch for general-purpose transparent toughening modification of PET according to claim 1, characterized in that, Catalysts and heat stabilizers are added during the melt polycondensation process.
4. The copolyester masterbatch for general-purpose PET transparent toughening modification according to claim 3, characterized in that, The catalyst is selected from at least one of tetrabutyl titanate, antimony trioxide, and antimony glycolate, and the amount added is 0.01 to 0.08% of the mass of terephthalic acid.
5. The copolyester masterbatch for general-purpose transparent toughening modification of PET according to claim 3, characterized in that, The heat stabilizer is selected from at least one of trimethyl phosphate and triphenyl phosphate, and the amount added is 0.01 to 0.05% of the mass of terephthalic acid.
6. The method for preparing copolyester masterbatch for general-purpose PET transparent toughening modification as described in any one of claims 1-5, characterized in that, Includes the following steps: Step 1, esterification reaction: Terephthalic acid and EG were added to a polymerization reactor at a molar ratio of 1:1.2-1.5 and esterified at 240-250℃ and 0.2-0.3MPa. The fraction was collected until the esterification rate was ≥95% to obtain the esterified product. Step 2, SPG prepolymerization: Add all SPG to the esterification product, along with a catalyst and a heat stabilizer; heat to 260–270°C and apply a gradient vacuum; first, maintain the temperature at 1000 Pa for 10–15 min to remove low-boiling substances, then reduce the pressure to <100 Pa and prepolymerize for 0.5–1.5 h to obtain the prepolymer. Step 3: BEPD final condensation polymerization: All BEPD is added to the prepolymer under normal or slightly positive pressure, the temperature is raised to 270-280℃, and polycondensation is carried out under vacuum <50Pa for 3-5 hours until the intrinsic viscosity of the product is 0.65-0.85dL / g; the product is discharged under nitrogen to break the vacuum, granulated by water cooling, and dried at 60-80℃ to obtain copolyester masterbatch.
7. The method for preparing copolyester masterbatch for general-purpose transparent toughening modification of PET according to claim 6, characterized in that, BEPD incorporates prepolymers under normal or slightly positive pressure to prevent loss during high-vacuum extraction.
8. A transparent toughened modified PET composition, characterized in that, Prepared by melt blending of general PET chips with copolyester masterbatch as described in any one of claims 1-5; the amount of copolyester masterbatch added is 5-40 wt% based on the total mass of the composition.
9. The transparent toughened modified PET composition according to claim 8, characterized in that, An ester exchange catalyst is added during the melt blending process; the ester exchange catalyst is selected from at least one of tetrabutyl titanate, zinc acetate, and manganese acetate, and the amount added is 0.05 to 0.2 wt% of the total mass of PET and copolyester masterbatch.